Early career researchers in the pandemic-fashioned ‘new scholarly normality’: voices from the research frontline - Nicholas, David; Herman, Eti; Boukacem-Zeghmouri, Cherifa; Watkinson, Anthony; Sims, David; Rodriguez-Bravo, Blanca; Świgon, Marzena; Abrizah, Abdullah; Xu, Jie; Serbina, Galina; Jamali, Hamid R.; Tenopir, Carol; et al. (El profesional de la información)
After two-years of talking to around 170 early career science/social science researchers from China, France, Malaysia, Poland, Russia, Spain, UK and US about their work life and scholarly communications during the pandemic, the Har-bingers-2 project is in possession of a mountain of verbatim data. The purpose of this paper is to highlight the kinds of comments ECRs are raising, with a focus on those that provide a particular interesting and illuminating take on ECRs’ experiences under difficult times. Comments, for instance, that might challenge the established order of things or that presage big changes down the line. The selection of comments presented here were made by the national interviewers shortly after the completion of the last of three rounds of interviews (two interviews in the case of Russia). The under-standings, appreciations and suggestions thus raised by the ECRs are insightful and constructive, which is what we might have expected from this cohort who are very much at the forefront of the research enterprise and veritable research workhorses. Sixteen broad scholarly topics are represented by quotes/comments, with the main focus of the comments on a subset of these: research performance and assessment, scholarly communication transformations, networking and collaboration, social media and access to information/libraries, which suggests, perhaps, where the action, concerns and interest mainly lie.